The Public Health Response to a Large Poisoning Outbreak Involving an Illicit Substance: Synthetic Cannabinoids Contaminated With a Long-Acting Anticoagulant Rodenticide, Illinois, March-July, 2018. Issue 6 (November 2020) - Navon, Livia; Moritz, Erin; Austin, Connie; Wahl, Michael; Aks, Steven; Layden, Jennifer
Abstract : During March-July 2018, the Illinois Department of Public Health responded to an acute outbreak of severe coagulopathy among patients with recent synthetic cannabinoid use. Toxicological testing indicated that cases were exposed to brodifacoum, a long-acting anticoagulant rodenticide. A total of 174 confirmed and probable cases, including 5 deaths, were linked to this outbreak. On the basis of the experience of responding to this complex outbreak, we recommend several steps for consideration to improve health department preparation for acute outbreaks involving illicit substances including strengthening communication between public health and law enforcement agencies, reviewing legal authority to investigate noninfectious acute disease outbreaks, continuing strong partnerships with state poison control centers, partnering with substance abuse and mental health agencies to provide services to patients, and determining health department ability to rapidly enter into public-private partnership agreements.